Efficency of local exhaust ventilation system and impact to indoor air quality in electroplating industry / Amir Omar - Omar, Amir (Faculty of Architecture, Planning and Surveying, 2012)
Electroplating industry is known as the industry that used chemicals in their process of production. Some of the chemicals uses in this industry are hazardous to health. Since the electroplating factory is the enclosed building, there for, the chemical which is used in the process would able to contribute to the indoor air pollution. Those employees who are working in this production area have potential to expose to chemical vapors. Local Exhaust Ventilation system is the mechanism of engineering control which is functioning to absorb the chemical generated from the process to the atmosphere. However, the efficiency of the Local Exhaust Ventilation may decrease due to poor maintenance program. The employers have responsibilities to ensure their Local Exhaust Ventilation is in good condition. Besides, those employees who may handle the hazardous chemical should be trained and aware on the chemical hazard and the impact of the risk to their health.